A Novel Multimodal Approach in AAU Resistant to Conventional Therapies and Tofacitinib: A Case Report - Sumit Kumar Bose (Apollo Medicine, 2026)
Introduction: Alopecia areata universalis (AAU) is a long-lasting, chronic, recurrent immune-mediated disease characterised by non-scarring hair loss of the scalp and other hair-bearing body areas. Even when treated with various treatments such as oral and topical steroids, anthralin, phototherapy and tofacitinib, recurrence is common after 6 months to 1 year. AAU presents with well-delineated, circumscribed patches of hair loss of the scalp. Remission is observed in 50% of cases within 1 year. Relapse may occur in 85% of cases, and alopecia universalis may occur in 14%–25% of cases. Nail abnormalities occur in severe cases. Family history is common and may occur in 21.8% of first-degree relatives. Case Report: A 35-year-old male with alopecia universalis presented to the outpatient department. He had AAU for 6 years and had various treatments that included topical and intralesional steroids, topical anthralin, minoxidil and oral tofacitinib, with temporary relief. The patient was started on oral upadacitinib 15 mg daily. After 3, 6 and 9 months, full growth of scalp, eyebrow and facial hairs was achieved. The patient was maintained on upadacitinib alone till last seen. Conclusion: Upadacitinib gives hope for the management of AAU to overcome treatment failures and challenges in recalcitrant cases.